Above-ground woody carbon sequestration measured from tree rings is coherent with net ecosystem productivity at five eddy-covariance sites - Babst, Flurin (The New phytologist, 2014)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.